Systematic Review and Meta-Analysis of Rituximab for Steroid-Dependent or Frequently Relapsing Nephrotic Syndrome in Children - Gao, Xia; Wang, Yan; Xu, Zichuan; Deng, Huiying; Yang, Huabin; Zhong, Fu (Frontiers in Pediatrics, 2021)
Objective To explore the effectiveness and safety of Rituximab (RTX) for steroid-dependent or frequently relapsing nephrotic syndrome via the systematic review and meta-analysis. Methods All the literature about RTX therapy for childhood nephrotic syndrome (NS) on PubMed, Web of Science, Cochrane Library, EMBASE and Chinese biomedical literature database published before November 1, 2019, were conducted and selected according to the preset criteria. Cochrane bias risk assessment tool was used to evaluate the quality of the literature included. The outcome data were analyzed by RevMan 5.3 software. Results There were 6 RCT researches that met the inclusion criteria with a moderate quality after evaluation. At the end of the treatment, the relapse rate of nephrotic syndrome in the RTX group reduced significantly when compared with that in the control [odds ratio (OR) = 0.11, 95% confidence interval (CI) (0.03, 0.43), P = 0.001]. The number of patients in the RTX group used less steroid or/and calcineurin inhibitors significantly than that in the control [OR=0.05, 95%CI (0.01, 0.28), P = 0.0007]. For children who were steroid-dependent, the RTX treatment significantly reduced the dosage of the steroid, compared with that in control [standardized mean difference (SMD) =-1.49, 95%CI (-2.00, -0.99), P <0.00001]. There was not a significant reduction in the protein execration between the two groups [SMD=-0.33, 95%CI (-0.71, 0.04), P=0.08]. Fewer serious adverse reactions of RTX in the 6 researches were reported and most adverse events were mild. Conclusion RTX is effective and safe for children with steroid-dependent or frequently relapsing nephrotic syndrome. Registration This review has been registered to the PROSPERO on 27 Feb 2020 (ID: CRD 42020150933).